Język ojczysty i jego znaczenie w procesie kumulowania kapitału kulturowego wśród migrantów na przykładzie Fundacji im. Władysława Reymonta - Jurczak, Agnieszka (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
This article concerns the cultural capital of Polish youth in Canada and the importance of Polish language knowledge in the context of accumulating this resource. It presents the results of sociological empirical research, which show that the ability to use the native language is related to the practice of specific habits that affect the ability to use and read cultural codes, the amount of economic resources and items related to the mother country, as well as having higher competences and more often declared social involvement. Therefore, knowledge of the Polish language influences the amount of cultural capital resources in an incorporated, objectified and institutionalized form.